The Trends of Foreign Employment and Remittance Inflow in Nepal - Pant, Ram Kumar (Journey for Sustainable Development and Peace Journal, 2024)
This paper discusses the employment situation of Nepalese youth in foreign countries and its impact on remittance. The main objective of this study is to assess the impact of foreign employment on remittance. This study is based on secondary data and quantitative analysis is adopted. The available data has been interpreted using descriptive statistics as well co-relation coefficient test. The study shows that the remittance inflow in the country has highly increased, though migration of youths has decreased compared to past years. There is a vast gap between male and female migrants. The number of male migrants is substantially high as compared to female migrants and the number of youth migrants going abroad for foreign employment is studied to be high in Gulf countries. The study further reveals that migration has a huge contribution to the nation’s economy as well as to the livelihood of their households with the inflow of remittance.